Disability Inclusive Public Service Delivery in Madhyapur Thimi Municipality: A Narrative Review - Pradhananga, Nisha (NPRC Journal of Multidisciplinary Research, 2025)
Madhyapur Thimi, a culturally rich municipality in Bhaktapur District, faces the critical task of ensuring public services are accessible to persons with disabilities (PWDs). This narrative review synthesizes findings from 30 scholarly articles, government reports, and organizational publications to explore the practices and challenges of disability-inclusive public service delivery in Madhyapur Thimi municipality. Key themes include policy frameworks, infrastructure accessibility, service provision, socio-cultural barriers, and stakeholder collaboration. This review identifies gaps in implementation and proposes strategies to enhance inclusivity, aligning with Nepal’s Rights of Persons with Disabilities Act, 2016, and the UN Convention on the Rights of Persons with Disabilities.